2020
DOI: 10.1155/2020/6097820
|View full text |Cite
|
Sign up to set email alerts
|

Low Vitamin D and Its Association with Cognitive Impairment and Dementia

Abstract: Vitamin D is a neurosteroid hormone that regulates neurotransmitters and neurotrophins. It has anti-inflammatory, antioxidant, and neuroprotective properties. It increases neurotrophic factors such as nerve growth factor which further promotes brain health. Moreover, it is also helpful in the prevention of amyloid accumulation and promotes amyloid clearance. Emerging evidence suggests its role in the reduction of Alzheimer’s disease hallmarks such as amyloid-beta and phosphorylated tau. Many preclinical studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 40 publications
1
51
0
2
Order By: Relevance
“…A study of Johansson et al supports this view as it showed an indirect association between lower 25(OH)D and acetylcholinesterase activity in cerebrospinal fluid [ 13 ]. Another mechanism that might play a role is the vitamin D-related upregulation of neurotrophic factors, such as NGF, GDNF, and NTF3 [ 11 ], which are also known to exert enhancing effects on cognition [ 5 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study of Johansson et al supports this view as it showed an indirect association between lower 25(OH)D and acetylcholinesterase activity in cerebrospinal fluid [ 13 ]. Another mechanism that might play a role is the vitamin D-related upregulation of neurotrophic factors, such as NGF, GDNF, and NTF3 [ 11 ], which are also known to exert enhancing effects on cognition [ 5 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The vitamin-D-supplemented group (supplement contained 4.0 μg (160 IU) of vitamin D and other trace elements) had a better cognitive performance ( p < 0.01) in the different cognitive tests (seven cognitive tests, including the MMSE) compared to the placebo group [ 174 ]. Another prospective pre–post interventional study, which included 80-year-old subjects from a memory clinic, found that those who received oral vitamin D3 supplementation (800 IU per day or 100,000 IU per month) experienced improved global cognition and executive functioning abilities over a 16-month follow-up period compared to controls [ 175 ]. Bailon et al [ 176 ], in its systematic review of meta-analysis cognition data (using the MMSE) provided suggestive evidence of a possible relationship between vitD and cognitive decline, but the nature of this relationship remained unclear.…”
Section: Neurogenesis Is Stimulated By Vitamin D Metabolites and Smentioning
confidence: 99%
“…In fact, adherence to proinflammatory dietary patterns was associated with greater cognitive decline [ 23 , 24 ], while dietary anti-inflammatory patterns reduce the inflammatory burden in periodontitis lesions [ 25 ]. Additionally, vitamin D deficiency has been growing attention reasonably in dementia [ 26 , 27 , 28 ] and periodontitis [ 29 ] since lower vitamin D intake associates with a higher risk of both conditions. However, the mediating role of inflammatory diet and vitamin D on the association of periodontal status and cognitive function has never been investigated.…”
Section: Introductionmentioning
confidence: 99%